A study on the factors of stress among the police officers at the District Police Headquarters in Pasir Puteh, Kelantan / Nur Sakinah Mohd Saidi and Noor Solehah Arifin - Mohd Saidi, Nur Sakinah; Arifin, Noor Solehah (2014)
With the today’s globalization, the police officers had faced many challenges in their worked which lead to stress. This could be proven with the study conducted on 2007 till 2009 which revealed that 53.7% out of 453 samples of police officers in Wilayah Persekutuan were experiencing stress and this policing profession was the most stressful compared to other occupations (Nasaruddin and Amirul, 2011). This research was performed to investigate the possible factors of stress among the police officers at the District Police Headquarters in Pasir Puteh, Kelantan. The survey design of single cross-sectional and the hypothesis testing were applied in this study. By using the proportionate stratified random sampling, the sample of about 66 police officers from four selected department which were department of crime, department of logistics, department of narcotics, and department of traffic involved in this study. The self-administered questionnaires had been employed to collect data. Then, the data were analyzed through the descriptive statistics and the Pearson correlation. The results had shown that there were no significant relationships between job burnout, shift worked, size of department and gender differences with the stress among police officers. The recommendations, limitations of the study, the scope for future research as well as the summary were provided in the report.